Ergonomic Assessment of Musculoskeletal Disorders\' Risk Factors in Construction Workers by PATH Method - Vida REZAEI HACHESU (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: work-related musculoskeletal disorders are the most common occupational injuries. This study was conducted to evaluate the risk factors for musculoskeletal disorders in construction workers. Methods: This descriptive cross-sectional study was conducted in 2017 among 82 construction workers in the West Azerbaijan Province. In this study the PATH method was used and the percentages of trunks, hands, feet, hand carriage activities, and tools used in the occupations was determined. To describe the data, descriptive statistics were applied. Results: The mean of age and working experience of the participants were 37.28 ± 6.68 and 11.94 ± 7.17 years, respectively. The highest body position was in the trunk (34.5 %), hands (55.8 %), and legs (50 %) were neutral. The maximum load weigh less than 5 kg (29 %). Conclusion: Construction is a widespread activity with multiple occupations and tasks associated with serious risk factors for musculoskeletal system. To improve the working conditions of these workers ergonomic interventions is necessary.